Comparing the Exteroceptive Feedback of Normal Stress, Skin Stretch, and Vibrotactile Stimulation for Restitution of Static Events - Motamedi, M. Reza; Florant, David; Duchaine, Vincent (Frontiers in Robotics and AI, 2017)
This paper investigates the effectiveness of three types of haptic feedback: normal stress, tangential force, and vibrotactile stimulation. Modern prosthetic limbs currently available on the market do not provide a wide range of sensory information to amputees, forcing amputees to mainly rely on visual attention when manipulating objects. We aim to develop a haptic system that can convey information to the central nervous system (CNS) through haptic feedback. To this end, we aim to find out which type of feedback performs best under static conditions, so that it can be used to restore a sense of grasping force to amputees. We tested the three main stimulation methods by inputting a series of five force magnitudes to each haptic device, so that the device applied the corresponding feedback to the participants’ finger pads. The participants then pressed on a force sensor, with the goal of applying the same level of force to a force sensor as they believed the haptic device had initially conveyed to them via their finger pads. While the subjects pressed on the force sensor, the haptic device applied a level of feedback to their forearms that corresponded to the pressure they were applying to the sensor. These tests provided fifteen numerical data per subject and a total of 180 trials for all twelve subjects. The end results indicate that even though all the stimulation methods provided a sufficient level of feedback, normal stress seems more effective than either tangential force or vibrotactile stimulation, at conveying the sense of pressure to the finger pad.